Achievements of Ukrainian mycology and microbiology as a basis for the development of space biotechnologies - Andrianova, T.V. (Problems of Environmental Biotechnology, 2023)
The achievements of Ukrainian mycology and microbiology, which can be used as a basis for the development of space biotechnologies, are considered.